Development of a Hybrid Decision Support System for Selecting the Air Filters Based on Multiple Criteria - Nguyen, Thi Thao Uyen; Nguyen, Vu Anh Duy; Nguyen, Huu-Tho; Ghazali, Ihwan (The Indonesian Institute of Science and Technology Research, 2024)
To select an air purifier that fully meets the needs of consumers, this study was conducted to provide the most objective and effective suggestions in making decisions and evaluating different smart purifier options that suit the tastes of users. Such decision-making is complicated for non-professionals when there are countless large and small brands on the market today with many different prices, features, and incentives. In such complex situations, decision-making with TOPSIS (Technique for Order of Preference by Similarity to Ideal Solution) can be used to eliminate risk and to better represent the preferences of decision-makers. From modeling to using the Entropy method and the TOPSIS method, all are done to serve the ultimate goal of choosing a good air purifier that meets the needs of customers.